On the weak localization principle of the eigenfunction expansions of the Laplace-Beltrami operator by Riesz method - Ahmedov, Anvarjon; Rasedee, Ahmad Fadly Nurullah (Institute for Mathematical Research, Universiti Putra Malaysia, 2015)
In this paper we deal with the problems of the weak localization of the eigenfunction expansions related to Laplace-Beltrami operator on unit sphere. The conditions for weak localization of Fourier-Laplace series are investigated by comparing the Riesz and Cesaro methods of summation for eigenfunction expansions of the LaplaceBeltrami operator. It is shown that the weak localization principle for the integrable functions f (x) at the point x depends not only on behavior of the function around x but on the behavior of the function around diametrically opposite point x.